Two Non-Awarded/Unrecognized Pravomils - in the Book by Jaroslav Čvančara and in the Novel by Petr Stančík - Hrtánek, Petr (Bohemica Olomucensia, 2023)
This article deals with two books, the subject of which was the life of the Czech resistance fighter Pravomil Raichl: the non-fiction publication by Jaroslav Čvančara Pravomil Raichl. Život na hranici smrti (Pravomil Raichl. Life on the Edge of Death, 2017), which presents Raichl's notable biography from a historiographical perspective (using historical sources and eyewitness accounts), and the novel by Petr Stančík Pravomil aneb Ohlušující promlčení (Pravomil or The Deafening Silence of Justice, 2021), which is inspired by the fate of the mentioned historical figure. The following article also tries to place both books in the context of the current perception of Czech modern history.
Keywords: Pravomil Raichl; modern history; monograph; Jaroslav Čvančara; novel; Petr Stančík